PROGNOSTIC SIGNIFICANCE OF PD-L1 EXPRESSION IN BREAST CANCER - Cirqueira, Magno Belém; Mendonça, Carolina Rodrigues; Soares, Leonardo Ribeiro; Cysneiros, Maria Auxiliadora de Paula Carneiro; Paulinelli, Régis Resende; Moreira, Marise Amaral Rebouças; Freitas-Junior, Ruffo de (Mastology, 2021)
The institution where the work was done: Hospital das Clínicas of the Universidade Federal de Goiás (UFG). Objective: To investigate the immunohistochemical expression of programmed cell death ligand 1 (PD-L1) in female invasive mammary carcinoma and to analyze the association of PD-L1 expression with clinicopathological characteristics, overall survival, and disease-free survival. Methodology: The expression of PD-L1 and its association with the main clinicopathological parameters have been evaluated in 232 cases. The Cox regression model was used to assess the possible association of PD-L1 expression with overall survival and disease-free survival. Results: A total of 58 cases (28.7%) were positive for PD-L1 expression. There is an association between PD-L1 expression with tumor size, negative hormone receptors, and triple-negative molecular subtype. Negative estrogen receptor and nodal status (≥10 positive lymph nodes) were associated with a reduction in overall survival, and the latter was associated with a lower disease-free survival. Luminal A tumor phenotype demonstrated a greater overall survival (p=0.042). Despite the significant association with unfavorable clinical and pathological characteristics in univariate and multivariate analyses, no significant correlation was observed between the expression of PD-L1 and overall or disease-free survival. Conclusions: Our data indicate that PD-L1 expression was associated with unfavorable clinical-pathological variables, such as greater tumor size, negative hormone receptors, and a greater number of metastatic nodes. No prognostic value was observed for the expression of PD-L1 in relation to overall survival or disease-free survival.